Posttraumatic Nonhemic Subdural Effusion - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The time course for the development of subdural fluid collections after a single traumatic event in 55 head trauma patients younger than 3 years was determined by CT scan in a retrospective consecutive case series at Children's Hospital of Wisconsin, Milwaukee.